2020
DOI: 10.1248/bpb.b19-00378
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Inhibits Human Renal Cell Carcinoma Cells Growth and Induces DNA Damage

Abstract: Pterostilbene (PTE) has inhibitory effect on a wide array of tumors. However, the therapeutic potential of PTE in renal cancer cells and the underlying mechanisms have not been evaluated. In this study, the aim is to demonstrate the growth inhibitory and the underlying mechanisms of PTE on human renal cell carcinoma (RCC) cells in vitro. By cell viability, cell morphology and colony formation assays, we found that PTE significantly suppressed the proliferation of RCC cells, while had little toxicity to the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Pterostilbene and baicalin are epigenetic modulators by suppressing histone deacetylase (HDAC) 1 expression [25,26], which contributes to histone hyperacetylation, and thus enhance gene expression [27]. Pterostilbene and scutellarein are also involved in DNA damage response [28,29], which is known to play a positive role in gene transcription initiation [30,31]. These compounds might regulate porcine HDP expression through epigenetic modification of HDP gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene and baicalin are epigenetic modulators by suppressing histone deacetylase (HDAC) 1 expression [25,26], which contributes to histone hyperacetylation, and thus enhance gene expression [27]. Pterostilbene and scutellarein are also involved in DNA damage response [28,29], which is known to play a positive role in gene transcription initiation [30,31]. These compounds might regulate porcine HDP expression through epigenetic modification of HDP gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene (trans-3,5-dimethoxy-4-hydroxystilbene, Figure 2) is a naturally derived compound found primarily in blueberries, but also in grapes and heartwood (Pterocarpus marsupium), that is commonly used for its antioxidant and anti-inflammatory properties [178][179][180]. Zhao et al [69] found that treatment with pterostilbene in A-498 and ACHN RCC cell lines potently induced cytotoxicity and apoptosis through upregulation of proapoptotic markers cyt. c, Bad, Bak, Bax, caspase-3, caspase-9, and PARP and downregulation of antiapoptotic Bcl-2.…”
Section: Pterostilbenementioning
confidence: 99%
“…Ivermectin (IVM) down-regulated the expression level of the anti-apoptotic protein Bcl-2 in the cytoplasm of HeLa cells, while the expression of the pro-apoptotic protein Bax exhibited dose-dependent effects [22]. In comparison to the control group, pterostilbene (PTE) increased the expression levels of pro-apoptotic proteins Bax, Cleaved-Caspase 3, and Cleaved-Caspase 9 in human renal cell carcinoma (RCC) cells and reduced the expression of the anti-apoptotic protein Bcl-2, indicating that PTE's inhibitory effect on RCC cell growth may be attributed to the induction of apoptosis [23]. Furthermore, CDK-4/-6 inhibitors arrest the cell cycle at the G1 phase and hinder the proliferation of aggressive cells, showing promise in attenuating the aggressiveness of breast cancers [24].…”
Section: Introductionmentioning
confidence: 99%